Estimation of the true suicide in Ecuador - Gorenc, Klaus-Dieter (1994)
The official statistical records on suicide are not reliable due to an under reporring of suicide cases. Considering that the true suicide count is the sum of the officia/ record plus the obscure cipher, an attempt was made to estimare the latter using a simple proporcional imputation formula. The official statistical records were re-analysed under the following racional: the category of violent death caused by acccident or intention, but where it could not be established for cerrain, served as a reservoir that contained the obscure cipher. Using this indirect technique, it was possible to determine that the percentage mean of the obscure suicide cipher (1970-1974) is lower than the showed in the literature.